Antitumor Activities of Aqueous Cinnamon Extract on 5637 Cell Line of Bladder Cancer through Glycolytic Pathway - Zeynab Aminzadeh; Nasrin Ziamajidi; Roghayeh Abbasalipourkabir; Sajedeh Daei; Sobhan Helbi; Abbas Moridnia (Hindawi Limited, 2022)
Background. Pharmacotherapy with medicinal plants is a promising approach to treat cancer. Cinnamon is a medicinal plant whose properties have been proven in various fields of medical sciences. Among its biological activities, its antioxidant and antiviral effects can be mentioned. In this study, the antitumor effects of Cinnamon with a focus on glucose metabolism in bladder cancer carcinoma cell-line 5637 were investigated. Methods. Aqueous extract of Cinnamon was prepared from Cinnamon bark. Bladder cancer 5637cell line were treated with different concentrations of aqueous extract of Cinnamon. MTT was used to evaluate cell viability at 24, 48, and 72 h. The concentration of 1.25, 2.50, and 5 mg/ml was used. Apoptosis was assessed with Hochest33258 staining. For evaluating of aqueous extract of Cinnamon effect on glycolysis, the gene expression of epidermal growth factor receptor 2 (ErbB2), heat shock protein transcription factor1 (HSF1), and lactate dehydrogenase A (LDHA), as well as protein levels of HSF1 and LDHA, LDH activity, glucose consumption, and lactate production, were measured. Results. Aqueous extract of Cinnamon significantly decreased ErbB2, HSF1, and LDHA gene expression and also decreased the protein level of HSF1 and LDHA, LDH activity, glucose consumption, and lactate production dose-dependently (p<0.05). Conclusion. Our finding showed that the aqueous extract of Cinnamon can inhibit proliferation in 5637 cells by inhibition of glycolysis and induction of apoptosis.